2020
DOI: 10.3390/ma13214945
|View full text |Cite
|
Sign up to set email alerts
|

Equibiaxial Strained Oxygen Adsorption on Pristine Graphene, Nitrogen/Boron Doped Graphene, and Defected Graphene

Abstract: We report first-principles calculations on the structural, mechanical, and electronic properties of O2 molecule adsorption on different graphenes (including pristine graphene (G–O2), N(nitrogen)/B(boron)-doped graphene (G–N/B–O2), and defective graphene (G–D–O2)) under equibiaxial strain. Our calculation results reveal that G–D–O2 possesses the highest binding energy, indicating that it owns the highest stability. Moreover, the stabilities of the four structures are enhanced enormously by the compressive strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Although there are few studies on oxygen adsorption, 13,16,36 the effect of the spin nature of the molecule on the electronic structure and the adsorption characteristics are not yet considered. The majority of the previous studies deal with adsorption on pristine graphene surfaces, other graphenebased materials, 14 and a few on transition metal doped 23,30 and on defective graphene.…”
Section: Adsorption Of Dioxygenmentioning
confidence: 99%
See 4 more Smart Citations
“…Although there are few studies on oxygen adsorption, 13,16,36 the effect of the spin nature of the molecule on the electronic structure and the adsorption characteristics are not yet considered. The majority of the previous studies deal with adsorption on pristine graphene surfaces, other graphenebased materials, 14 and a few on transition metal doped 23,30 and on defective graphene.…”
Section: Adsorption Of Dioxygenmentioning
confidence: 99%
“…Using the computational rstprinciples technique, Nakamura et al 26 found that oxygen atoms selectively adsorb on intrinsic graphene, forming epoxide rings and modifying structural and electrical characteristics. There have been a few experimental 5,[27][28][29] and theoretical attempts 13,16,[30][31][32][33][34][35][36][37] to explore the sensing of molecular dioxygen, O 2 , on pristine and doped graphene monolayers. Some earlier literature reveals attempts to make oxygen sensors 27,28 with monolayer graphene.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations